P126 TRANSVERSE MYELITIS AFTER VEDOLIZUMAB INDUCTION. (18th January 2018) - Hong, Simon J; Agrawal, Manasi; Lukin, Dana
Abstract: A 36-year-old woman with ankylosing spondylitis (AS) and a 12 year history of moderate, extensive ulcerative colitis (UC) was evaluated for active symptoms after a 15 month hiatus. Prior therapy included mesalamine and infliximab; the latter led to clinical improvement but was discontinued after a severe infusion reaction. Evaluation revealed active moderate UC, and vedolizumab therapy was initiated with induction doses at weeks 0 and 2. At week 5, she developed ascending bilateral upper extremity paresthesias, muscle weakness and headaches. MRI revealed C3-5 enhancement (image), consistent with transverse myelitis (TM). There were no preceding upper respiratory or pulmonary symptoms. CSF was positive for Mycoplasma (1:32), WBC count (18/uL) and oligoclonal bands (>5); other work-up was negative. She improved with IV corticosteroids for five days, with full resolution of symptoms and MRI changes at 8 months. She is currently in clinical and biochemical remission on 6-MP and mesalamine. Vedolizumab, approved for moderate-severe UC and CD in 2014, is a humanized anti-α4β7 integrin monoclonal antibody that blocks gut-specific lymphocyte trafficking and is associated with minimal adverse effects such as nasopharyngitis and mild upper respiratory infections. Its predecessor natalizumab blocks α4β1 and α4β7 integrins, additionally limits lymphocyte-trafficking to the blood-brain barrier and is associated with progressive multifocal leukoencephalopathy. Vedolizumab is rarely associated with arthritis and sacroileitis but not with CNS disease. While TM has been reported with anti-TNFα agents, this is the first case associated with vedolizumab, possibly as an immune phenomenon or reactivation of Mycoplasma infection. While it could be incidental, given the patient's history of AS and prior infusion-reaction to anti-TNF therapy, the temporal association with vedolizumab calls for caution.